Reflections on the Spatial Performance of Atom Probe Tomography in the Analysis of Atomic Neighborhoods - Gault, Baptiste; Klaes, Benjamin; Morgado, Felipe F.; Freysoldt, Christoph; Li, Yue; De Geuser, Frederic; Stephenson, Leigh T.; Vurpillot, François (Microscopy and microanalysis, 2022)
Atom probe tomography (APT) is often introduced as providing “atomic-scale” mapping of the composition of materials and as such is often exploited to analyze atomic neighborhoods within a material. Yet quantifying the actual spatial performance of the technique in a general case remains challenging, as it depends on the material system being investigated as well as on the specimen's geometry. Here, by using comparisons with field-ion microscopy experiments, field-ion imaging and field evaporation simulations, we provide the basis for a critical reflection on the spatial performance of APT in the analysis of pure metals, low alloyed systems and concentrated solid solutions (i.e., akin to high-entropy alloys). The spatial resolution imposes strong limitations on the possible interpretation of measured atomic neighborhoods, and directional neighborhood analyses restricted to the depth are expected to be more robust. We hope this work gets the community to reflect on its practices, in the same way, it got us to reflect on our work.